Identification of Key mRNAs as Prediction Models for Early Metastasis of Pancreatic Cancer Based on LASSO - Xue, Ke; Zheng, Huilin; Qian, Xiaowen; Chen, Zheng; Gu, Yangjun; Hu, Zhenhua; Zhang, Lei; Wan, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Pancreatic cancer is a highly malignant and metastatic tumor of the digestive system. Even after surgical removal of the tumor, most patients are still at risk of pancreatic cancer metastasis. Therefore, screening for biomarkers for pancreatic cancer metastasis and suggest precise therapeutic intervention targets. In the study, we included 96 samples from The Cancer Genome Atlas (TCGA) with no metastasis or metastasis after R0 resection of pancreatic cancer. We also retrieved data of metastatic pancreatic cancer cell lines from Gene Expression Omnibus (GEO), as well as collected sequencing data from our own cell lines BxPC-3 and BxPC-3-M8. Then the expression of metastasis-related genes in different datasets was analyzed by “Limma” or “edgeR” packages in R software, and enrichment analysis of differential genes was used to explore the potential mechanism of pancreatic cancer metastasis. Finally, six genes were identified as risk factors for predicting metastatic status by LASSO regression, including Zinc Finger BED-Type Containing 2 (ZBED2), S100 calcium binding protein A2 (S100A2), Hagged canonical Notch ligand 1 (JAG1), Laminin subunit gamma 2 (LAMC2), transglutaminase 2 (TGM2) and HLF transcription factor (HLF). We used these six EMT-related genes to construct a risk scoring model. The receiver operating characteristic (ROC) curve showed that the risk score could better predict the risk of patient metastasis. Univariate and multivariate Cox regression analyses revealed that the risk score was also an important predictor of pancreatic cancer. In conclusion, 6-mRNA expression may be a potential metastatic molecular biomarker in pancreatic cancer and provide a valuable method for predicting pancreatic cancer metastasis, assessing clinical outcomes, and facilitating future personalized treatment for patients with ductal adenocarcinoma of the pancreas (PDAC).